Investigation of potential effects of aronia melonacarpa supplementation on sportive performance - Pancar, Z.; Alincak, F. (The Eurasia Proceedings of Health, Environment and Life Sciences, 2023)
Nowadays, people's interest in more natural resources and aromatic plants has started to increase in terms of natural and healthy nutrition. Recently, the demand for medicinal plants rich in polyphenols with antimicrobial and antioxidant properties has increased. Aronia (Aronia melanocarpa) has recently become one of the most preferred fruits due to its high antioxidant activity and rich polyphenol content. The aim of this study was to investigate the potential effects of Aronia supplementation on athletes and its mechanisms of action from a specific point of view. For this purpose, a literature review was conducted and information was compiled with current studies by searching through aronia supplementation and sportive performance. It is seen that Aronia melanocarpan is used in many aspects. It has been evaluated in the treatment of many diseases, including colds and stomach diseases, as well as intestines, gall bladder and liver. Since it increases the level of good cholesterol, it has also been used to combat heart disease and cardiovascular problems. As a result of the literature researches, it can be said that aronia melanocarpan is used for therapeutic purposes in many diseases, but the studies in terms of sportive performance are limited. More studies are needed to reveal the effects of this supplement on sportive performance.